Environmental science sustaining the earth - Miller, G. Tyler (George Tyler) 1931- (Wadsworth biology series, 1992)
This book is designed to be used in introductory courses on environmental science. It treats environmental science as an INTERDISCIPLINARY study, combining ideas and information from natural sciences such as biology, chemistry, and geology and social sciences such as economics, politics, and ethics to present a general idea of how nature works and how things are interconnected. It examines how the environment is being used and abused, and what individuals can do to protect and improve it for themselves, for future generations, and for other living things.